Burnout among midwives and attitudes toward midwifery: a cross-sectional study from Baden-Württemberg, Germany [research data] - Paul, Nicolas; Limprecht-Heusner, Marcus; Eichenauer, Jutta; Scheichenbauer, Christel; Bärnighausen, Till; Kohler, Stefan (Universität, 2024)
Introduction: Midwifery services are a cornerstone of maternal care, but the mental health of midwives is at risk in many work settings. The aim of this study was to assess burnout and attitudes toward midwifery among midwives in Baden-Württemberg, Germany. Methods: A cross-sectional online survey among midwives was conducted from 16 October to 10 December 2017. Burnout was assessed using the Copenhagen Burnout Inventory (CBI). Results: A total of 602 survey respondents were studied; 48.3%, 38.2%, and 23.3% of midwives reported moderate or high (CBI score ≥50) levels of personal burnout, work-related burnout, and client-related burnout, respectively. Midwives with moderate or high burnout in at least one CBI dimension worked more weekly hours, were more commonly employed, and worked more frequently in the hospital. In turn, midwives with low burnout levels worked fewer weekly hours, more commonly freelance, and more frequently community based (all p<0.001). Moderate or high burnout levels were associated with a reduced likelihood to recommend midwifery as a profession (OR=0.34; 95% CI: 0.23-0.49) and an increased likelihood to intent leaving the profession (OR=3.39; 95% CI: 2.0-5.9) in a multivariable regression adjusting for midwife characteristics and work practices. Conclusions: Burnout symptoms were common among midwives. Burnout could be a health risk for midwives and a challenge to the profession by discouraging present and future midwives from practicing midwifery.
Gesehen am 29.05.2024
Keywords: Forschungsdaten; Datenbank